The Regulation of Whole Body Protein Metabolism Following Exercise in Children - Volterman, Kimberly A. (My University, 2016)
General nutritional strategies to promote whole body protein retention, particularly with relation to exercise, have been largely based on adult research that does not consider the dynamic process of growth and often ignores scenarios commonly experienced by children (e.g., exercise in the heat). Therefore, the aim of the experiments outlined in this thesis was to investigate the importance of post-exercise protein quantity and timing in active children, specifically with respect to whole body protein turnover. Chapter 4 demonstrated that a whole-food protein-containing beverage can impact whole body protein balance (WBPB) in healthy children following exercise. Specifically, consuming ~0.40 g·kg-1 of protein in the form of skim milk enhanced whole body nitrogen turnover (Q) and protein synthesis, resulting in a less negative WBPB compared with a carbohydrate electrolyte solution (CES) and water (W) over 16 h. It was also found that puberty and sex significantly affected WBPB. In order to elucidate the specific effects of protein, participants in Chapter 5 were provided with isoenergetic mixed macronutrient beverages containing graded levels of protein (0 g·kg-1, ~0.18 g·kg-1, and ~0.32 g·kg-1) following an acute bout of exercise. Net protein balance was increased in a dose-dependent manner early in recovery, but in order to sustain a net anabolic environment over an entire 24 h period it appears that larger protein intakes (~0.32 g·kg-1) are required. Finally, in Chapter 6 [1-13C]leucine infusion was used to confirm previous conclusions. Following an acute bout of exercise, graded levels of protein (0 g·kg-1, ~0.12 g·kg-1, ~0.22 g·kg-1and ~0.33 g·kg-1) acutely increased whole body leucine balance in a dose-dependent manner. However, in order to attain a positive WBPB over 24 h, multiple protein feedings following exercise may be more important than the absolute quantity of protein ingested in the post-exercise period.
Keywords: protein metabolism; exercise; children; adolescents